Development of a biomimetic arch-like 3D bioprinted construct for cartilage regeneration using gelatin methacryloyl and silk fibroin-gelatin bioinks. (1st July 2023) - Chakraborty, Juhi; Fernández-Pérez, Julia; van Kampen, Kenny A; Roy, Subhadeep; ten Brink, Tim; Mota, Carlos; Ghosh, Sourabh; Moroni, Lorenzo
Abstract: In recent years, engineering biomimetic cellular microenvironments have been a top priority for regenerative medicine. Collagen II, which is arranged in arches, forms the predominant fiber network in articular cartilage. Due to the shortage of suitable microfabrication techniques capable of producing 3D fibrous structures, in vitro replication of the arch-like cartilaginous tissue constitutes one of the major challenges. Hence, in the present study, we report a 3D bioprinting approach for fabricating arch-like constructs using two types of bioinks, gelatin methacryloyl (GelMa) and silk fibroin-gelatin (SF-G). The bioprinted SF-G constructs displayed increased proliferation of the encapsulated human bone marrow-derived mesenchymal stem cells compared to the GelMA constructs. Biochemical assays, gene, and protein expression exhibited the superior role of SF-G in forming the fibrous collagen network and chondrogenesis. Protein-protein interaction study using Metascape evaluated the function of the proteins involved. Further GeneMANIA and STRING analysis using Col 2A1, SOX 9, ACAN, and the genes upregulated on day 21 in RT-PCR, i.e. β -catenin, TGF β R1, Col 1A1 in SF-G and PRG4, Col 10A1, MMP 13 in GelMA validated our in vitro results. These findings emphasized the role of SF-G in regulating the Wnt/ β -catenin and TGF- β signaling pathways. Hence, the 3D bioprinted arch-like constructs possess a substantial potential for cartilage regeneration.